2014
DOI: 10.1155/2014/261804
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Hedgehog Signaling and Clinical Outcome in Osteosarcoma

Abstract: Despite the importance of Hedgehog signaling in bone development, the relationship between Hedgehog pathway expression and osteosarcoma clinical characteristics and outcome has not been investigated. In this study of 43 high-grade human osteosarcoma samples, we detected high expression levels of the Hedgehog ligand gene, IHH, and target genes, PTCH1 and GLI1, in most samples. Further analysis in tumors of patients with localized disease at diagnosis identified coexpression of IHH and PTCH1 exclusively in large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 30 publications
1
39
1
Order By: Relevance
“…Osteosarcoma (OS) is the most common bone cancer in children and young adults, affecting around 400 children in the US every year 1,2 . OS is a malignant neoplasm of the bone having a high propensity for pulmonary metastasis with approximately 20% of patients diagnosed with metastatic tumors and 80% developing metastasis despite standard of care treatment including surgery and chemotherapy 3,4 . Less than 15% of patients with metastatic OS experience 5-year survival rates with current non-targeted treatments, and, over the last three decade there was little improvement in survival rates [5][6][7][8] .…”
mentioning
confidence: 99%
“…Osteosarcoma (OS) is the most common bone cancer in children and young adults, affecting around 400 children in the US every year 1,2 . OS is a malignant neoplasm of the bone having a high propensity for pulmonary metastasis with approximately 20% of patients diagnosed with metastatic tumors and 80% developing metastasis despite standard of care treatment including surgery and chemotherapy 3,4 . Less than 15% of patients with metastatic OS experience 5-year survival rates with current non-targeted treatments, and, over the last three decade there was little improvement in survival rates [5][6][7][8] .…”
mentioning
confidence: 99%
“…In contrast to focused clinical genetic tests such as FISH, genomic profiling using next-generation DNA sequencing offers the ability to characterize genetic lesions genome-wide, with base-pair resolution necessary to confidently ascribe pathogenic functions. Indeed, clinical genomic profiling utilized in this case revealed deletions of genes characteristically inactivated in osteosarcomas, such as RB1, ATRX , and PTCH1 [13,14]. Thus, genomic profiling enhanced clinical diagnosis, leading to more precise therapy selection, given substantial differences in current treatment regimens for osteogenic and Ewing sarcomas [11].…”
Section: Discussionmentioning
confidence: 99%
“…In a small cohort of 12 patients at diagnosis, expression of SMO, PTCH1 and Gli2 transcripts were variously increased [126]. Recently, an exploratory study of surgical biopsies of 43 high-grade OS also revealed high gene expression of IHH, PTCH1 and Gli1, and moderated expression of SMO, normalized to normal osteoblast samples [127]. The levels of IHH, SMO, PTCH1 and Gli1 were correlated with each other in small tumors, indicative of a ligand-independent activation whereas ligand-dependent activation of the HH pathway was suggested in large tumors, as high expression of IHH and PTCH1 were correlated.…”
Section: Shh Signaling In Os Et Esmentioning
confidence: 99%